2019
DOI: 10.1017/jfm.2019.343
|View full text |Cite
|
Sign up to set email alerts
|

On the detection of internal interfacial layers in turbulent flows

Abstract: A novel approach to identify internal interfacial layers, or IILs, in wall-bounded turbulent flows is proposed. Using a Fuzzy Cluster Method (FCM) on the streamwise velocity component, a unique and unambiguous grouping of the Uniform Momentum Zones is achieved, thus allowing the identification of the IILs. The approach overcomes some of the key limitations of the histogram-based IIL identification methods. The method is insensitive to the streamwise domain length, can be used on inhomogeneous grids, uses all t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…Panels ( c – g ) show at the series of streamwise locations denoted in panel ( a ) by vertical black lines, where panels ( c – g ) correspond to monotonically increasing locations. The logarithmic law is superimposed upon the panels, for reference, while clear UMZs were visually detected and are highlighted with annotations (more sophisticated UMZ identification methods are available, but this is not the purpose of the present paper; Fan et al 2019). The observed UMZs in panels ( c – g ) correlate with the intersection of parcels of quasi-uniform momentum in panel ( a ): consider, for example, the momentum deficits at ( d ) and ( e ), or the momentum excesses at ( f ) and ( g ).…”
Section: Results From Dns Of High- Channel Flowmentioning
confidence: 99%
“…Panels ( c – g ) show at the series of streamwise locations denoted in panel ( a ) by vertical black lines, where panels ( c – g ) correspond to monotonically increasing locations. The logarithmic law is superimposed upon the panels, for reference, while clear UMZs were visually detected and are highlighted with annotations (more sophisticated UMZ identification methods are available, but this is not the purpose of the present paper; Fan et al 2019). The observed UMZs in panels ( c – g ) correlate with the intersection of parcels of quasi-uniform momentum in panel ( a ): consider, for example, the momentum deficits at ( d ) and ( e ), or the momentum excesses at ( f ) and ( g ).…”
Section: Results From Dns Of High- Channel Flowmentioning
confidence: 99%
“…The channel core exhibited significant thinning, thickening and meandering behaviour; it occasionally extended very close to the channel walls and left the centreline outside the core (≈7 % of the time overall). A recent study by Fan et al (2019) proposed a new method to identify the internal shear layers bounding the UMZs. The method does not require user-defined parameters as for the PDF approach to UMZ identification and is insensitive to the streamwise domain length.…”
Section: The Existence and Detection Of Umzmentioning
confidence: 99%
“…Beginning with the seminal work of Meinhart & Adrian (1995), an increasing number of laboratory (de Silva, Hutchins & Marusic 2016; de Silva et al 2017), field (Priyadarshana et al 2007) and computational (Lee & Moser 2015, 2018; Fan et al 2019) studies have revealed the remarkable tendency for turbulent wall flows to self-organize into regions of quasi-uniform streamwise momentum segregated by internal layers of concentrated spanwise vorticity. As shown in figure 1( a ), taken from the experiments of de Silva et al (2016), the resulting arrangement of uniform momentum zones (UMZs) and internal shear layers, which we refer to as vortical fissures (VFs), causes the instantaneous wall-normal () profile of streamwise ( velocity to exhibit a staircase-like structure.…”
Section: Introductionmentioning
confidence: 99%